2008
DOI: 10.1177/039463200802100321
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Desensitization in Patients with Wasp Venom Allergy: Preliminary Results

Abstract: The aim ofthis paper is to assess in an open prospective pilot case-control study the tolerability, safety and efficacy of an ultra-rush sublingual immunotherapy (SLIT) protocol with Vespula venom in wasp allergic patients compared to subcutaneous immunotherapy (SCIT). Forty-one wasp allergic patients were treated with sublingual (SLIT group) or subcutaneous (SCIT group) ultrarush immunotherapy with Vespula venom extract. All patients underwent skin tests and serum specific IgE and IgG 4 detection before enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Venom immunotherapy (VIT), delivered by the subcutaneous route, has been used successfully for many years and is the current recommended gold standard treatment for subjects with severe insect sting allergy associated with anaphylaxis [27,52]. Two small studies exploring the sublingual route [30,31] showed some benefit but larger trials are needed. The severity of previous reactions informs the choice of VIT as a correlation is established between the frequency of systemic reactions to subsequent stings and the severity of previous reactions, with 40-60% risk of further severe reactions in subjects who have experienced prior anaphylaxis [53].…”
Section: Hymenoptera Venom Allergymentioning
confidence: 99%
See 1 more Smart Citation
“…Venom immunotherapy (VIT), delivered by the subcutaneous route, has been used successfully for many years and is the current recommended gold standard treatment for subjects with severe insect sting allergy associated with anaphylaxis [27,52]. Two small studies exploring the sublingual route [30,31] showed some benefit but larger trials are needed. The severity of previous reactions informs the choice of VIT as a correlation is established between the frequency of systemic reactions to subsequent stings and the severity of previous reactions, with 40-60% risk of further severe reactions in subjects who have experienced prior anaphylaxis [53].…”
Section: Hymenoptera Venom Allergymentioning
confidence: 99%
“…Randomized controlled trials (RCT) of SCIT and SLIT showed clinical efficacy, further confirmed by meta-analyses [13,[22][23][24][25] and systematic reviews [26][27][28][29]. SCIT is effective in preventing systemic and large local allergic reactions to insect stings [27] with some data indicating similar success with the sublingual route [30,31]. Recent studies and subsequent meta-analysis have shown that AIT may be effective for atopic dermatitis (AD) [32] and food allergy [23].…”
mentioning
confidence: 91%
“…In reply to Patriarca et al, 1 we acknowledge the fact that we did not refer to their publication 2 in our recent comment on the study by Severino et al 3 However, we omitted the study by Patriarca et al 2 deliberately, because this study also does not present data that show effectiveness of sublingual venom immunotherapy (SL-VIT).…”
Section: Replymentioning
confidence: 93%
“… 90 An observational study of wasp SLIT in 2 1 patients showed good tolerability and suggested possible efficacy. 91 An observational study of bee venom SLIT suggested reduced LLR in the majority of patients treated. 92 A single randomized controlled trial of SLIT VIT was identified in the Cochrane review: 19 there was no evidence that SLIT was less effective than SCIT for reducing risk of SR or LLR in that review, although this preliminary conclusion was based on a small number of studies and participants.…”
Section: Future Perspectivesmentioning
confidence: 99%